Pedagogical discourse and communication ethic in policultural virtual educational environment - Grigory A. Rozhkov; Yulia V. Taratuhina; Lubov A. Tsyganova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The COVID-19 pandemic has served as a catalyst for the transition of education to an online format. Clearly, most educational institutions and teachers were forced to adapt methods and forms of online educational process on the short notice. The issue of online education has long been considered from the scientific and practical sides, however, such a quick and forced transition to online revealed the problems, features and potential of online communication. The ethics of online communication in education is one of the most significant issues. The development of the information environment initiated the emergence of an educational multicultural environment, which entailed a certain kind of systemic changes, which, one way or another, will be reflected in the transformation of the elements of the information and educational environment (IEE) organization. This applies to both the traditional format of education and online educational practices. There is a number of specific features of multicultural educational environment that do not occur in monocultural environments: non-identical professional thesauri, various habitual communication patterns with a teacher, representation of educational information and educational content specifics, decision-making specifics, the attitude to creative tasks performing in the process of learning, ambiguous understanding of learning objectives, terminology, preferred type of control and measuring materials, etc.